Changes in the tarsal conjunctiva viewed by in vivo confocal microscopy are associated with ocular symptoms and contact lens wear. (28th August 2019) - López‐de la Rosa, Alberto; Alghamdi, Waleed M; Kunnen, Carolina ME; Lazon de la Jara, Percy; González‐García, María J; Markoulli, Maria; Papas, Eric B
Abstract: Purpose: To investigate the effect of soft contact lens (CL) wear on the morphology of the epithelial‐lamina propria junction as well as the possible association with symptoms of discomfort. Methods: Ninety‐two subjects were recruited, including 60 soft CL wearers, 16 previous wearers, and 16 non‐wearers. Additionally, subjects were classified as symptomatic or asymptomatic using the Contact Lens Dry Eye Questionnaire 8 for the CL wearers (a score ≥ 12 was considered symptomatic) and the Dry Eye Questionnaire 5 for the previous wearers and non‐wearers (a score ≥ 5 was considered symptomatic). In vivo confocal microscopy of the tarsal conjunctiva was performed on a single occasion. Papillae density, shortest diameter, longest diameter, area, circularity, lumen/wall brightness ratio, irregularity, reflectivity, inhomogeneous appearance of wall and inhomogeneous appearance of rete ridges were evaluated. Effects of CL wear, symptoms and their interaction were analysed using two‐way analysis of variance. Correlations were investigated using Spearman's coefficient. Data are presented as mean (standard deviation) or median [interquartile range]. Results: Contact lens wearers, compared to previous wearers and non‐wearers, showed higher circularity [0.65 (0.08) vs 0.59 (0.10) vs 0.57 (0.11), p = 0.003]. Subjects with symptoms, compared to asymptomatic participants, showed higher circularity [0.64 (0.08) vs 0.61 (0.10), p < 0.001] and lower irregularity (1.0 [0.7–2.0] vs 1.3 [1.0–2.3], p = 0.009). For previous wearers, those with symptoms showed greater density (135.4 [107.3–183.3] vs 87.5 [85.4–116.7], p = 0.013) and circularity [0.64 (0.07) vs 0.54 (0.10), p = 0.016]. For non‐wearers, those with symptoms showed higher circularity [0.65 (0.08) vs 0.50 (0.08), p < 0.001]. DEQ‐5 correlated with circularity (ρ = 0.55, p = 0.001). Conclusions: Soft CL wear modifies papillae of the epithelial‐lamina propria junction into a more rounded shape; however, CL cessation appears to resolve this alteration. Additionally, a more rounded papillae shape is associated with ocular symptoms in subjects not actively wearing CLs.